Hunting for livelihoods by farmers in the lowland forests of Papua’s Bird’s Head Peninsula, Indonesia - AGUSTINA YOHANA SETYARINI AROBAYA; JOHN R. M. APITULEY; AUGUST E. PATTISELANNO; GUN MARDIATMOKO; FREDDY PATTISELANNO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Arobaya AYS, Apituley JRM, Pattiselanno AE, Mardiatmoko G, Pattiselanno F. 2025. Hunting for livelihoods by farmers in the lowland forests of Papua’s Bird’s Head Peninsula, Indonesia. Biodiversitas 26: 2375-2382. Rural people in Indonesian Papua hunt on a part-time basis to supplement livelihoods. Although hunting plays an important role in local livelihood, the profile of hunters in Papua is not really well understood. Therefore, this study aimed to examine indigenous hunting practices across 11 villages of Tambrauw District on the lowland coast of the Bird’s Head Peninsula, Papua, Indonesia. Data were collected from 1020 hunters to assess practices in supporting local livelihoods along the coast, and populated by small-scale farmers who currently produce food mainly for local consumption. Hunting was not typically the main source of revenue, because majority of hunters were employed full-time in another field, while performed alternate hunting for additional cash. The results showed that about 69% of respondents were farmers, hunting intermittently to gain extra income, with small plot holders hunting more frequently. Aims of hunting varies, with 49.02% of respondents hunting to supply market demand, 43.73% of respondents hunting for family consumption, and other estimated 7.26% reported hunting for cultural reasons and crop protection. Active hunting with spears, knives, bows, and arrows was the most common hunting practices, while hunting with guns, was the least used in the study villages. Hunting was mostly in primary forests (34.22%), with introduced species deer (37.25%) and wild pig (31.37%) being the most hunting target. Finally, hunter-farmers performed hunting to meet the requirement for an animal protein source to supply family consumption and the bushmeat market demand. Introduced species such as deer and wild pigs contribute significantly to the hunting practices in this study, because they have a higher economic value, with both meat and fat playing a crucial role in meeting the family animal protein need. Hunting patterns at the lowland coastal forests of the Bird’s Head Peninsula were similar to other tropical forest sites, to some degree had a significant impact on the hunting practices across the lowland coastal forests.